Articulação entre conhecimento neurocientífico e inovação pedagógica: possíveis contribuições ao ensino de física na educação superior - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This research is based on the following problem: How are the didactic-methodological approaches of the Physics degree course at UNIPAMPA – Bagé Campus presented through the lenses of Pedagogical Innovation and Neurosciences? To this end, in order to answer the problem, the aim is to understand whether the didactic-methodological approaches used by the Physics Degree course at the Bagé Campus are anchored in the Pedagogical Innovation and Neurosciences bias. We opted for a qualitative approach to the research, characterizing it as exploratory in terms of its objectives, and bibliographical, documentary and field research in terms of the technical procedures used. This study was divided into four methodological stages, the first of which was the bibliographic survey, which aimed to investigate how the scientific literature on methodological approaches to teaching physics in higher education is presented in the light of pedagogical innovation; the second stage comprises documentary research, which aimed to investigate how pedagogical innovation is presented in the didactic-methodological approaches of the Pedagogical Projects of the Physics Degree Course at the Bagé Campus; the third stage is the field research, which aimed to investigate possible indicators of pedagogical innovation in the reports of teachers, students and graduates of the Physics Degree course at the Bagé Campus, and to this end, an online questionnaire was sent to the aforementioned research subjects; the fourth methodological stage refers to the analysis of the results obtained in the previous stage, which was divided into two moments: the first is the treatment of the data by means of the Content Analysis proposed by Laurence Bardin; the second is the inference of the pedagogical innovation bias, according to the assertions of innovation for Higher Education according to Flávia Wagner and Maria Isabel da Cunha, as well as the neuroscientific inference about the methodological approaches reported by the teachers, students and graduates. The results made it possible to discuss those found in the 2018 and 2022 PPCs, as well as inferring the pedagogical innovation bias in them; in addition to the categories of analysis for discussing the results of the field research, which made it possible to create two thematic categories: one on innovative teaching practice and the other on the contribution of Neuroscience to Physics Teaching. Finally, it was shown that the objectives proposed for each of the stages of the research were achieved, in addition to highlighting some limiting factors in the development of the study, as well as future possibilities for the research. The study also concludes that the didactic-methodological approaches of the Physics degree course are on the horizon of innovation and can be improved through neuroscientific knowledge.
Keywords: Inovação pedagógica; Neurociência; Licenciatura em física; Innovación pedagógica; Neurociencia; Licenciatura en física; Pedagogical innovation; Neuroscience; Degree in physics; CNPQ::CIENCIAS HUMANAS